Discordance Between Plasma and Intratumoral Estradiol in Treatment-Naïve Luminal Breast Cancer: A Cross-Sectional Study - Arga Scorpianus Renardi; Widyanti Soewoto; Brian Wasita (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Estradiol drives luminal breast cancer, and plasma estradiol is widely used as a systemic marker; whether it reflects the intratumoral hormonal milieu is uncertain. This study evaluated the relationship between plasma and intratumoral estradiol and their demographic determinants in treatment-naive luminal breast cancer. Methods: An observational analytical cross-sectional study was conducted at Dr. Moewardi Regional General Hospital and the Anatomical Pathology Laboratory, Universitas Sebelas Maret, Surakarta, Indonesia (2019-2024). Fifty-six treatment-naive patients with Luminal A or Luminal B breast cancer were enrolled by total sampling. Plasma estradiol was measured by enzyme-linked immunosorbent assay and intratumoral estradiol by immunohistochemistry; data were analysed with Spearman correlation, chi-square/Fisher tests, logistic regression and ROC analysis, with effect sizes and 95% confidence intervals. Results: Plasma estradiol did not correlate with intratumoral estradiol (Spearman rho = 0.136; 95% CI -0.13 to 0.39; p = 0.319) and discriminated tissue positivity at chance level (AUC = 0.42; 95% CI 0.25-0.59). Age >=50 years (OR 7.27; 95% CI 2.01-26.29; p = 0.001) and postmenopausal status (OR 11.61; 95% CI 2.85-47.38; p < 0.001) were associated with high plasma estradiol, and postmenopausal status remained independent after adjustment (adjusted OR 11.16; 95% CI 2.68-46.54). Neither variable was associated with intratumoral estradiol (p = 0.863 and p = 0.665). Conclusion: Systemic estradiol does not represent the tumour hormonal state in luminal breast cancer; intratumoral estrogen appears governed by local intracrine mechanisms. Tumour-specific assessment may guide endocrine therapy more accurately than plasma measurement alone.